2007
DOI: 10.1111/j.1524-475x.2007.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Why chronic wounds will not heal: a novel hypothesis

Abstract: The present paper presents a hypothesis aimed at explaining why venous leg ulcers, pressure ulcers, and diabetic foot ulcers develop into a chronic state. We propose that the lack of proper wound healing is at least in part caused by inefficient eradication of infecting, opportunistic pathogens, a situation reminiscent of chronic Pseudomonas aeruginosa infections found in patients suffering from cystic fibrosis (CF). We have analyzed sections from chronic wounds by fluorescence in situ hybridization and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
592
0
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 760 publications
(618 citation statements)
references
References 106 publications
8
592
0
18
Order By: Relevance
“…Recent studies have shown how P. aeruginosa non-attached biofilm aggregates form in liquid batch cultures, and that they have the same characteristics as surface attached biofilms when it comes to antibiotic tolerance and resilience towards PMNs [62,63]. The absence of such surfaces in surface wounds means the bacterial cells assume a biofilm lifestyle within a self-contained aggregate, devoid of surface attachment [64,65]. There have been a number of in vitro studies that have observed steep chemical gradients (notably oxygen) throughout biofilms, which leads to a heterogenic growth pattern [26,32].…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…Recent studies have shown how P. aeruginosa non-attached biofilm aggregates form in liquid batch cultures, and that they have the same characteristics as surface attached biofilms when it comes to antibiotic tolerance and resilience towards PMNs [62,63]. The absence of such surfaces in surface wounds means the bacterial cells assume a biofilm lifestyle within a self-contained aggregate, devoid of surface attachment [64,65]. There have been a number of in vitro studies that have observed steep chemical gradients (notably oxygen) throughout biofilms, which leads to a heterogenic growth pattern [26,32].…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…Within an infected wound, bacterial pathogens frequently exist within protective structures termed biofilms (Bjarnsholt et al, 2008;James et al, 2008). Biofilms are embedded in a glycocalyx, which is a combination of bacterial secreted extracellular polysaccharides that form a protective matrix adhering to the host's surrounding tissues (Stoodley et al, 2002;Sutherland, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…7 Bjarnsholt T and et al said that pseudomonas plays the important role in diabetic foot infection. 8 George et al stated that diabetes accounts for up to 50 per cent of non-traumatic leg amputations. Foot ulceration unattended is the most common single precursor to amputation.…”
Section: Discussionmentioning
confidence: 99%